THE FINANCIAL INCLUSION OF ISLAMIC BANKING FOR LOW-INCOME COMMUNITIES: CASE STUDY IN WEST SUMATERA - Neng Kamarni; Hefrizal Handra; Muslich Anshori (Universitas Airlangga, 2022)
This study aims to analyze the prospects and perspectives of low-income people in West Sumatra on financial inclusion in Islamic banking. Also, this study analyzesvarious factors that determine Islamic banking's financial inclusion and assesses the level of public expectations of the financial inclusion of Islamic banks in West Sumatra. This study applies descriptive quantitative research with primary data. Statistical toolssuch as Mann-Whitney Rank Sum U-test, Kruskal Wallis test, weighted arithmetical mean, chi-square test, and one-way ANOVA are used to reach the research's objectives. As a result, gender, age, marital status, monthly income, type of work, and status in the household are not significantly related to the level of customer expectations of financial inclusion. However, there is a significant relationship between the level of education and type of bank with the level of customer expectations of financial inclusion. The study results illustrate that low-income people in West Sumatra are familiar with Islamic banking, but many of them have not chosen to have an account in Islamic banking. The fatwa of the Council of Ulama Indonesia (MUI) and the Islamic banking system are not fully understood by the people of West Sumatra, the majority of whom are Muslims. A bank account selection is based on ease of reach and location. However, the public's view of Islamic banks is very high, as can be seen from people's expectations that Islamic banks provide a high sense of justice and comfort.